2021
DOI: 10.3389/fmars.2020.602972
|View full text |Cite
|
Sign up to set email alerts
|

Marine Important Bird and Biodiversity Areas for Penguins in Antarctica, Targets for Conservation Action

Abstract: Global targets for area-based conservation and management must move beyond threshold-based targets alone and must account for the quality of such areas. In the Southern Ocean around Antarctica, a region where key biodiversity faces unprecedented risks from climate change and where there is a growing demand to extract resources, a number of marine areas have been afforded enhanced conservation or management measures through two adopted marine protected areas (MPAs). However, evidence suggests that additional hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 110 publications
(173 reference statements)
0
19
0
Order By: Relevance
“…Furthermore, all studies including ours have reported that juveniles visit the highly productive ACC area during their first journey at sea, where the Antarctic Polar Front appears to act as an ecological barrier. During the most vulnerable stage of their life, the penguins' dispersive behaviour leads them outside the SO-Treaty and CCAMLR limits into waters where they are likely to encounter and compete with fisheries (see [ 29 , 51 ] for current data on fisheries activity). In addition, overlap with fisheries in the Weddell Sea region might occur in forthcoming decades and increase the threat to emperor penguins according to the projected long-term effects of climate change on krill population migration [ 24 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, all studies including ours have reported that juveniles visit the highly productive ACC area during their first journey at sea, where the Antarctic Polar Front appears to act as an ecological barrier. During the most vulnerable stage of their life, the penguins' dispersive behaviour leads them outside the SO-Treaty and CCAMLR limits into waters where they are likely to encounter and compete with fisheries (see [ 29 , 51 ] for current data on fisheries activity). In addition, overlap with fisheries in the Weddell Sea region might occur in forthcoming decades and increase the threat to emperor penguins according to the projected long-term effects of climate change on krill population migration [ 24 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The emperor penguin is considered an iconic and ecologically important species of Antarctica. Its colony sites and at-sea movements have been the basis of previous discussions of conservation priorities, either in terms of MPAs [ 4 ], important bird areas [ 28 , 29 ] or areas of ecological significance [ 30 ]. With a population currently estimated at ca 270 000 breeding pairs in 61 known colonies around the continent [ 27 ], the species is severely threatened by global warming and expanding fishing activities in the Southern Ocean [ 15 , 31 ], facing the risk to be nearly extinct within this century [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…This could make it more difficult to reach net-zero emissions [2,3,83]. The potential for animal-borne devices to reveal areas of use and therefore potential for overlap with marine renewables is great [26,[84][85][86][87]. However, there are ethical and logistical concerns associated with tagging wild animals, as well as time and resource constraints to consider when analyzing the complex data retrieved from the devices [17,41,79].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are ethical and logistical concerns associated with tagging wild animals, as well as time and resource constraints to consider when analyzing the complex data retrieved from the devices [17,41,79]. Additionally, while such data have been used in marine conservation and management previously (e.g., [26,85]), this is often at a scale (i.e., ocean-basin) less immediately relevant to developers and stakeholders in marine renewables. In order to facilitate its use within the assessment of risk to animals from marine renewable energy, we developed an analysis workflow ( Figure 2) and applied it to archival biologging and telemetry data for six European shags within a major tidal development area.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of tracking data from Southern Ocean seabirds, and penguins in particular, has been widely used to define important areas for marine conservation in Antarctic waters. Many of these studies have focused exclusively on birds incubating or provisioning chicks, an energetically demanding period when nest duties restrict the foraging ranges of breeding adults (Dias et al, 2018; Handley et al, 2021; Warwick‐Evans et al, 2018). During other life‐history stages birds may have larger foraging distributions with very different spatial overlaps between conspecifics, including breeding animals from adjacent or distant colonies, other marine predators and potential threats, such as fisheries.…”
Section: Introductionmentioning
confidence: 99%